G354(P) 'bridges and barriers': Middle grade perspectives about contacting on-call general paediatric consultants. (27th April 2016) - Calvert, A; West, N; Elder, C
Abstract : Background: Effective communication is recognised as a cornerstone of good medical practice and is key to maintaining patient safety. Poor communication is often highlighted as a factor in medical errors. Despite structured communication tools (e.g. SBAR) and guidelines to encourage collaborative working between middle grade trainees (MGT) and on-call consultants (OCC) in many trusts, there is a paucity of information about this communication pathway and specifically which positive (bridges) and negative (barriers) factors play an influential role. Aims: To explore perceptions of MGT about contacting the OCC. To examine factors about MGT, consultants, hospital environment and working structure, which facilitate or obstruct communication. Methods: Following a pilot study, an anonymous on-line questionnaire was distributed to all MGT in a large deanery in 2015. Demographic data, experience regarding bridges and barriers to communication and clinical scenarios were collected in addition to free text comments. Results: To date 61 MGT have responded (25.2% response rate): 72% female, 80% UK-trained, 61% full-time. 56% reported having time out of training. When presented with 10 scenarios, all respondents would contact the OCC in the case of a child death, most for safeguarding and few in the case of failed practical procedures. When analysing the statements the strongest agreement was with "I feel able to ask for help when I need it", "I find it easier to phone for advice when I know the consultant is in the hospital" and "effective communication with the OCC is harder if they have missed handover". 32 respondants (52%) reported experience of consultants being resident out of hours (OOH). Two-thirds agreed this provided increased learning opportunities, improved patient safety and experience. Themes identified as bridges included approachability, clear expectations and attending handover. Not knowing the patients and not being readily accessible acted as barriers to communication. Conclusion: This is the first study of its kind. The surveyed MGT were generally confident in their communication with OCC and identified bridges and barriers which may aid more effective communication pathways, improving patient safety and trainee job satisfaction. Consultant presence both at handover and OOH were highlighted as important.